The Effect of Covid-19 on Voters in the Medan Tuntungan District Election in 2020 - Nizar Nazlia; Tonny P. Situmorang; Indra Fauzan (Universitas Medan Area, 2023)
The Covid Sickness (Coronavirus) flare-up that happens in all nations in this present reality is progressively widespread. This instance of pneumonia of obscure etiology or Coronavirus was first recognized in Wuhan City, Hubei Area, China on December 31, 2019. Medan City is one of the regions that held regional elections for the mayoral election, In the 2020 Medan city election, Medan was included in the red zone area where one of the areas with a positive number of covid-19 reached 4,261 people with this number Medan city accounting for 75 percent of corona virus cases in North Sumatra. But in fact, with the large number of positive Covid-19 cases in the city of Medan, there is no decrease in public enthusiasm to come to the Polling Station (TPS) compared to previous elections in Medan. This study uses a type of quantitative research because this study seeks to analyze whether there is an influence of the COVID-19 pandemic on voter participation in Medan Tuntungan sub-district. This type of research is a type of descriptive research. Influence of Covid-19 on Voters in the Medan Tuntungan District Election in 2020 is as follows: Voter participation in Medan Tuntungan District is also influenced by other variables outside the Covid-19 pandemic variable, which is 83.8%, so it is appropriate if research related to voter participation is carried out again using other variables outside the Covid-19 pandemic variable.